Beau Geste Press: A Liminal Communitas Across the New Avant-Gardes - Pujol-Duran, J (UNIV VALENCIA, DEPT PREHISTORIA & ARQUEOLOGIA, 2018)
In this article I will examine how a few Latin American avant-garde artists and poets in exile became part of Fluxus, an international constellation of artists whose ideas revitalised the concept of the avant-garde after the war. This constellation became an active collaboration through the makings of the Beau Geste Press, founded in Devon (UK) in 1971 and active until 1976. The press, co-founded by Felipe Ehrenberg, Martha Hellion and David Mayor, not only published and disseminated the work of Cecilia Vicuna, Ulises Carrion, Claudio Bertoni, and Ehrenberg himself, but also operated as "a community of duplicators, printers and craftsmen" that replaced the concept of individual creation with a practice of communal production. I will refer to Victor Turner s concept of liminality to contend that the Beau Geste Press, which represented the beginning and end of this communitas, developed in a space that was liminal on different levels: at the level of the subjective experience of exile; of artistic production, which can be inferred from their emphasis on procedural techniques over finished artistic products; and at the level of language, because they are Spanish-speaking authors in England, who turn that potential problem into hybrid forms.